Reduced dry season fish biomass and depleted carnivorous fish assemblages in unprotected tropical oxbow lakes - Barocas, A; Araujo Flores, J; Alarcon Pardo, A; Macdonald, DW; Swaisgood, RR (Elsevier, 2021)
The effectiveness of protected areas in maintaining biodiversity is increasingly under debate. Specifically, the responses of animal populations in freshwater ecosystems to disturbances outside protected areas are not well understood. Fish assemblages can serve as an indicator of such responses. We used dry season oxbow lake fish occurrence data implemented within a Measurement of Biodiversity framework to examine the influence of extractive activities on the richness, structure and abundance of fish assemblages. We compared oxbow lakes in protected areas with lakes subject to artisanal small-scale gold mining (ASGM) and other human activities. The main components of fish biodiversity maintained by lake protection were abundance and biomass. The strongest predictors of community structure were fishing intensity and water transparency. As variation in these factors are likely a consequence of ASGM, our results may indicate indirect impacts of ASGM on freshwater ecosystems. Our analysis of fish trophic guilds also suggested that carnivores dominated fish assemblages in protected lakes, whereas in disturbed lakes detritivores were more frequent, suggesting a trophic downgrading of freshwater ecosystems subject to ASGM. Taken together, our results indicate responses of fish assemblages to human activity associated with ASGM. In the western Amazon, protected and isolated areas appear to be successful at maintaining the integrity of fish assemblages. Given the vulnerability of freshwater habitats and their high value for ecosystem services, we recommend local community engagement and resource allocation to prevent the degradation of oxbow lake habitats and the depletion of local aquatic biodiversity in unprotected areas.